Aplikacje mobilne w akademickiej dydaktyce językowej na przykładzie wykorzystania platformy Duolingo w nauczaniu języka rosyjskiego - Gajda, Katarzyna (Neofilolog, 2024)
In the last decade, there has been a marked increase in interest in the use of mobile technologies in education, especially in language teaching. In the context of Mobile Assisted Language Learning (MALL), mobile applications offer unique features such as personalization, interactivity, and access to online resources, promoting individual language learning processes and supporting traditional teaching methods. This article focuses on the analysis of the effectiveness of the Duolingo application in teaching Russian at the University of Warsaw. The study was conducted in the summer semester of 2021/2022 with a group of 78 students. The results confirmed the positive impact of Duolingo on student engagement and the efficiency of material assimilation, while emphasizing the need for technical and educational support for the full use of the application. Study participants were keen on using Duolingo, particularly appreciating the reading lessons, although exercises aimed at developing speaking and writing skills were perceived as less effective. The conclusions of the study indicate the need for further research on the application of Duolingo in foreign language teaching and the analysis of its materials in the context of glottodidactics.